45.2k views
3 votes
Factor the expression below.

Factor the expression below.-example-1
User Alexis
by
5.4k points

1 Answer

4 votes

Answer:

D.
(9x-10)(9x+10)

Explanation:

We need to factor the given expression
81x^2-100


81x^2-100


=9^2x^2-10^2

Apply formula
a^x*b^x=(a*b)^x


=(9x)^2-10^2

Apply formula
a^2-b^2=(a+b)(a-b)


=(9x+10)(9x-10)


=(9x-10)(9x+10)

Hence final answer is choice D.
(9x-10)(9x+10)

User Helvete
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.